Psikoedukasi Kesiapan Bekerja bagi Mahasiswa - St. Hadjar Nurul Istiqamah; Novita Maulidya Jalal (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract: This study aims to determine the effect of psychoeducation on students' readiness to work. This research method is One Group Pretest Postetst Design. The sampling technique was purposive sampling as many as 20 students. The technique of collecting data was through a questionnaire survey. The technique of analyzing quantitative descriptive data. The results of the study revealed that based on the data obtained after psychoeducation was given to the subject, it was known that 45.5% of the subjects felt very ready to work. 81.8% stated that they obtained a lot of new knowledge related to work readiness, and 83% stated that psychoeducation was very useful for work readiness.